CRITERIA FOR THE DIAGNOSIS OF FELINE DIABETES MELLITUS - Jacinto, Adria Amanda Carvalho; da Silva, Ronald Erick Lobo; Ferreira, Caroline Gracielle Torres; da Silva, Pedro Henrique Andreatti (Seven Editora, 2026)
Feline diabetes mellitus (DM) is a complex endocrinopathy whose pathophysiology, in most cases, mimics human type 2 diabetes mellitus, being characterized by a combination of peripheral insulin resistance and progressive dysfunction of pancreatic β cells (Taylor et al., 2025). Clinical evidence indicates that approximately 20–25% of cases are associated with hypersomatotropism (HST), frequently resulting from functional pituitary adenomas, which significantly contributes to refractory insulin resistance (Taylor et al., 2025; Miceli et al., 2022). The traditional therapeutic framework, historically centered on insulin therapy, has evolved substantially. Insulin glargine 300 U/ml (IGla-U300) presents relevant pharmacodynamic advantages, including a more stable and prolonged action profile, with less glycemic variability (Linari et al., 2022). Clinical studies demonstrate its effectiveness in reducing hyperglycemia and serum fructosamine levels, as well as promoting significant remission rates, particularly in newly diagnosed cats with a low risk of clinical hypoglycemia (Linari et al., 2022). In parallel, sodium-glucose cotransporter 2 (SGLT2) inhibitors, such as bexagliflozin and velagliflozin, represent a therapeutic innovation by promoting glycemic control independent of insulin secretion through the induction of glycosuria (Cook; Behrend, 2024). Although they improve treatment adherence and reduce glucotoxicity, their use requires careful patient selection and rigorous monitoring due to the risk of euglycemic diabetic ketoacidosis (eDKA) (Cook; Behrend, 2024; Taylor et al., 2025). The clinical evolution of feline DM is strongly influenced by comorbidities. Pancreatitis establishes a bidirectional relationship with the disease, contributing both to its genesis and to metabolic instability (Xenoulis; Fracassi, 2022). In cases of feline diabetes mellitus (DM) associated with hypersomatotropism (HS), cabergoline, a D2 dopaminergic agonist, has demonstrated efficacy in reducing IGF-1 concentrations, improving insulin sensitivity, and inducing remission in a significant proportion of patients (Miceli et al., 2022). (Ronald Lobo) Additionally, continuous glucose monitoring (CGM) has transformed clinical follow-up, allowing for dynamic assessment of glycemic variability and reducing interferences associated with stress-induced hyperglycemia (Taylor et al., 2025). Thus, the contemporary management of feline DM is based on an integrated approach that combines pharmacological advances, comorbidity control, and technological monitoring.